2017
DOI: 10.1272/jnms.84.224
|View full text |Cite
|
Sign up to set email alerts
|

Worse Preoperative Status Based on Inflammation and Host Immunity Is a Risk Factor for Surgical Site Infections in Colorectal Cancer Surgery

Abstract: Objective: The modified Glasgow Prognostic Score (mGPS) is an inflammation-based measure of malnutrition that reflects a state of cachexia in cancer patients. We evaluated mGPS as an index to predict surgical site infection (SSI) incidence in patients undergoing colorectal cancer surgery. Subjects and Methods:We retrospectively analyzed 351 patients who underwent colon cancer resection. Factors correlated with the incidence of SSIs were identified by logistic analysis and stepwise selection.Results: SSIs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 22 publications
(23 reference statements)
0
26
0
Order By: Relevance
“…In the present study, the AAC level had a close relationship with the GPS and mGPS, and this level reflects the systemic inflammatory response. The systemic inflammatory response may be worse because of malnutrition and reduced preoperative immunocompetence, suggesting that compromised immunocompetence may influence infections . The GPS was also reported as the better predictive system in patients with HCC after living donor LT in our population .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In the present study, the AAC level had a close relationship with the GPS and mGPS, and this level reflects the systemic inflammatory response. The systemic inflammatory response may be worse because of malnutrition and reduced preoperative immunocompetence, suggesting that compromised immunocompetence may influence infections . The GPS was also reported as the better predictive system in patients with HCC after living donor LT in our population .…”
Section: Discussionmentioning
confidence: 66%
“…The systemic inflammatory response may be worse because of malnutrition and reduced preoperative immunocompetence, suggesting that compromised immunocompetence may influence infections. (15,16) The GPS was also reported as the better predictive system in patients with HCC after living donor LT in our population. (17) Therefore, the finding that a high AAC level leads to poorer survival and a high systemic inflammatory response is highly compelling.…”
Section: Discussionmentioning
confidence: 68%
“…The CONUT score is also associated with poor survival in patients with hepatitis B virus reactivation [19]. In addition, it has been reported to predict the prognosis of patients with various cancers, including gastric cancer, colon cancer, and pancreatic cancer [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed clinicopathological factors associated with RI, as categorized in a previous report 5 . We also calculated prognostic nutritional index (PNI) 6 , neutrophil lymphocyte ratio (NLR) 7 , and controlling nutritional status (CONUT) 8 , and mGPS, as previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…Infectious complications are classified into surgical site infections (SSIs) and remote infections (RIs), which differ in pathogenesis 4 . We previously reported that cachexia is an independent risk factor for SSI using mGPS as an index 5 . However, among infectious complications, whether or not cachexia affects only SSI remains inconclusive 4 .…”
Section: Introductionmentioning
confidence: 99%